Contaminação microbiana em hemodiálise e sua associação ao risco de infecções - Caparelli, Laura Maria Barros (2019)
Chronic diseases such as hypertension, diabetes mellitus, and chronic glomerulonephritis are the main causes that can lead to chronic renal failure (CRF), which consists of an injury that causes progressive and irreversible loss of renal function. The main treatments for CRI are peritoneal dialysis, hemodialysis and renal transplantation. In the hemodialysis system has been considered as a source of growth of microorganisms and may offer risks to patients undergoing treatment. Thus, this study aimed to survey the cases of microbiological contamination of the hemodialysis system, reported during the period from 1985 to 2017. The retrospective, secondary study looked for articles in the databases U.S. National Library of Medicine, Scientific Electronic Library Online, Latin American and Caribbean Literature in Health Sciences, using descriptors in Portuguese / English and Spanish. A total of 35 articles were selected after applying the inclusion and exclusion criteria. In 56% of the articles, the presence of bacteria with Gram-negative prevalence was identified, in 21%, the presence of fungi, in 10% mycobacteria were reported in 10%, bacteria were not named and in 3%, Gram-positive bacteria were described. It was observed a higher prevalence of Gram-negative bacteria of the genus Pseudomonas, but there was also a meeting of bacteria such as Escherichia coli, Burkholderia cepacia and Enterobacter cloacae. Some of the fungi identified were the genera Aspergillus and Penicillium, in addition to the species Candida parapsilosis. In addition to fast-growing mycobacteria, Gram-positive bacteria such as Bacillus thuringiensis and Staphylococcus hyicus were also identified. It is concluded that measures are needed to combat the proliferation of pathogenic microorganisms in the hemodialysis system, minimizing the risks and health problems of the patients who undergo this treatment.